2006
DOI: 10.1111/j.1600-0781.2006.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of NB‐UVB in both segmental and non‐segmental vitiligo affecting different body sites

Abstract: The type of vitiligo, the affected anatomical area and the disease duration are important factors that influence potential re-pigmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
115
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 27 publications
9
115
2
1
Order By: Relevance
“…Another observation from our study is that patients with grade 4 improvement had a shorter disease duration compared to patients with grade 0 improvement. This finding is similar to previous studies [19,22,23]. Therefore, it is advisable to initiate treatment as early as possible once the diagnosis of vitiligo has been confirmed.…”
Section: Discussionsupporting
confidence: 92%
“…Another observation from our study is that patients with grade 4 improvement had a shorter disease duration compared to patients with grade 0 improvement. This finding is similar to previous studies [19,22,23]. Therefore, it is advisable to initiate treatment as early as possible once the diagnosis of vitiligo has been confirmed.…”
Section: Discussionsupporting
confidence: 92%
“…In our series 18 and in the study by Anbar et al, 17 a statistically significant difference was documented. Lesions on acral sites (hands and feet) always show minimal response 3,6,9,11,[13][14][15][16][17][18] and in one study 17 this observation was statistically confirmed. The reason behind this anatomic variation in response to treatment is unclear, but it may be related to the regional variation in the density of hair follicles, which have been shown to be reservoirs for melanocytes.…”
Section: Nb-uvb Efficacymentioning
confidence: 64%
“…51 There seems to be no association between response to treatment and patients' sex, 3,9,18 age, 3,9,15,18 positive family history of vitiligo, 9,18 and body surface area affected. 9,18 The association between response to treatment and duration of vitiligo is unclear: some studies report such an association, 14,16,17 whereas others do not. 3,9,18 An earlier response to treatment has been correlated to a higher level of posttreatment repigmentation.…”
Section: Nb-uvb Efficacymentioning
confidence: 96%
See 1 more Smart Citation
“…13 Lesions on the hands and feet (ie, acral vitiligo) have typically been the most difficult to treat with medical modalities. 8,14 Anbar et al 15 reported repigmentation of between 0% and 25% after treating 39 patients with acral lesions with 6 months of narrowband ultraviolet B. Considering 22% of patients achieved excellent results (and 22% receiving good repigmentation and 22% receiving fair pigmentation), there may be a particular role for the MKTP in management of vitiligo involving certain parts of the hands and feet where the tips of the fingers and toes are not involved.…”
Section: Discussionmentioning
confidence: 93%